2021
DOI: 10.1038/s41598-021-01915-x
|View full text |Cite
|
Sign up to set email alerts
|

The brain’s structural differences between postherpetic neuralgia and lower back pain

Abstract: The purpose is to explore the brain’s structural difference in local morphology and between-region networks between two types of peripheral neuropathic pain (PNP): postherpetic neuralgia (PHN) and lower back pain (LBP). A total of 54 participants including 38 LBP and 16 PHN patients were enrolled. The average pain scores were 7.6 and 7.5 for LBP and PHN. High-resolution structural T1 weighted images were obtained. Both grey matter volume (GMV) and morphological connectivity (MC) were extracted. An independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Similarly, we found a correlation between pain interference and SN segregation, suggesting that, as DAN, altered response in this network could be a contributing factor to the maintenance and chronicity of pain. SN also exhibits task- and resting-state abnormalities in some CP populations ( Otti et al, 2013 ; Becerra et al, 2014 ; Cauda et al, 2014 ; Qiu et al, 2021 ), and may be dysregulated due to constant pain ( Borsook et al, 2013 ), giving rise to a “salient state,” mostly divided into two processes: bottom-up saliency and top-down control ( Melloni et al, 2012 ). Nonetheless, it is well justified that there is an association between a dysregulated SN and the interplay between pain symptoms and psychological aspects, as several studies have also seen before ( Legrain et al, 2011 ; Coppieters et al, 2016 ; van Ettinger-Veenstra et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found a correlation between pain interference and SN segregation, suggesting that, as DAN, altered response in this network could be a contributing factor to the maintenance and chronicity of pain. SN also exhibits task- and resting-state abnormalities in some CP populations ( Otti et al, 2013 ; Becerra et al, 2014 ; Cauda et al, 2014 ; Qiu et al, 2021 ), and may be dysregulated due to constant pain ( Borsook et al, 2013 ), giving rise to a “salient state,” mostly divided into two processes: bottom-up saliency and top-down control ( Melloni et al, 2012 ). Nonetheless, it is well justified that there is an association between a dysregulated SN and the interplay between pain symptoms and psychological aspects, as several studies have also seen before ( Legrain et al, 2011 ; Coppieters et al, 2016 ; van Ettinger-Veenstra et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TA had increased dReHo values in the Left superior temporal gyrus, middle frontal gyrus, precentral gyrus, precuneus, angular gyrus, right superior frontal gyrus, middle temporal gyrus, postcentral gyrus, middle frontal gyrus. The middle frontal gyrus is thought to be related to the dispose of pain, and in more pain-related studies, abnormal changes in the middle frontal gyrus, such as migraine, postherpetic neuralgia, and lower back pain ( 44 46 ). Research have shown that the frontal cortex has the role of information integration, which can link pain and related behaviors, mainly involved in the integration and processing of pain information, and the frontal gyrus of TA patients is activated, which is related to the processing and integration of pain information.…”
Section: Discussionmentioning
confidence: 99%
“…The university staff were so used to the physical working culture and had difficulties in managing their first time working remotely. Most employees also need to cope with the absence of ergonomic office furniture at home and the inconvenient workspace at home has led them to have problems like musculoskeletal (MSK) disorders problem (Qiu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%